The Concept of Pedagogy in the Quran - bin Mukhtar, Zulkefly; Norazimah binti Mukhtar; Azwan bin Harun (International Journal of Advanced Multidisciplinary, 2022)
Islam is a perfect religion where its teachings include all the rules in organizing the affairs of human life related to the world and the hereafter. The great guide book bestowed by Allah s.w.t through Rasulullah s.a.w became the guide of all mankind. In the Qur'an is also told about pedagogy that can be a reference for educators. The formula and theory of educational goals in the perspective of the Qur'an consists of several aspects namely tarbiyah jismiyah (physical education), tarbiyah ruhiyah (spiritual education), tarbiyah 'aqliyah (cognitive education), tarbiyah wijdaniyah (emotional education), tarbiyah khuluqiyah (moral education) and tarbiyah ijtima'iyyah (social education). The method of analogy (tamthil) is also effective in providing parables in delivering lessons. In addition, many pedagogies can be taken in surah al-Alaq and surah Luqman for educator guidance. Islam directs all the potential of human nature to be developed and developed integrated between spiritual and physical in order to be a holistic human being.